Wellbeing and job satisfaction among employees with intellectual disability - Joyce, Andrew; Campbell, Perri; Crosbie, Jenny; Wilson, Erin (Frontiers in Public Health, 2025)
ObjectivesThe workplace is considered one of the key settings in which to promote health and wellbeing. Reviews of workplace health promotion have shown that workplace interventions can positively impact on mental health, nutrition, and physical activity, and can impact positively on economic indicators such as absenteeism. One of the research gaps is workplace health promotion for people with an intellectual disability. This is an important gap to address as people with an intellectual disability have higher rates of avoidable mortality relative to the general population, increased rate of mental health problems, lower levels of physical activity, and poorer nutrition. People with an intellectual disability work across a range of industries and employment settings and it is important to understand potential strategies in supporting the health and wellbeing of this cohort within workplaces.MethodsForty-seven in-depth interviews were conducted with staff and supported employees from four organizations to examine job satisfaction and wellbeing experiences in the workplace and potential strategies for supporting health and wellbeing of people with an intellectual disability.ResultsThe findings revealed that currently there is a strong emphasis on strategies such as mentoring and support, flexible approaches, and customized and varied roles to support mental wellbeing. There seems to be less focus on physical activity and nutrition with limited examples of strategies addressing these topics. There are also instances of bullying being experienced in open employment settings.ConclusionsFurther work is required to verify whether these results are consistent across the sector, but it does seem to illustrate that workplace wellbeing intervention models and strategies that are applicable in workplaces for the general population may not necessarily work in employment settings that are inclusive of people with an intellectual disability. The policy implication is that support structures so important to health and wellbeing within supported employment settings also need to be available in open employment environments. Further research and policy work is required to develop specific models and strategies that will be applicable to this population cohort within supported and open workplace settings.